Analisis Fitokimia Dan Uji Potensi Ekstrak Etanol Kulit Batang Matoa (Pometia pinnata L) Sebagai Antibakteri Terhadap Pertumbuhan Escherichia coli - Djois Sugiaty Rintjap; Elvie Rifke Rindengan; Selfie Petronella Joice Ulaen; Evelina Maria Nahor; Rilyn Novita Maramis (Journal of Pharmaceutical and Sciences, 2026)
Background: Diarrhea is a health condition, can be caused by Escherichia coli bacteria. Matoa bark has pharmacological activity, can be used as an alternative antibacterial treatment from natural ingredients. Objective: to determine the content of phytochemical compounds and the potential of ethanol extract of matoa bark as an antibacterial against the growth of Escherichia coli. Method: Type of laboratory experiment research, maceration method extraction, 95% ethanol, test solution concentrations of 10%, 20%, 30%. positive control Ciprofloxacin, negative control aquadestilata. Phytochemical analysis based on color reactions and sediment. Antibacterial potential test disc diffusion method, inhibition zone measured using calipers, observation 1x24 hours. Results: Ethanol extract of matoa bark contains phytochemical compounds flavonoids, triterpenoids, saponins, tannins. The extract concentrations of 10%, 20%, and 30% have antibacterial activity with an average inhibition zone diameter of 15.75±0.39 mm, 16.09±0.19 mm, and 18.14±0.73 mm, respectively, which are classified as strong. The diameter of the inhibition zone for Ciprofloxacin is 29.56±0.30 mm. The higher the concentration of the extract, the larger the inhibition zone. Conclusion: The ethanol extract of matoa (Pometia pinnata L) stem bark contains phytochemical compounds flavonoids, triterpenoids, saponins, and tannins. Concentrations of 10%, 20%, and 30% have antibacterial activity against Escherichia coli, which are classified as strong. The best test results were obtained at a concentration of 30%.